Photo-Oxidation of Desaspidin Sensitized by Chlorophyll - Hind, Geoffrey (1966)
The uncoupler desaspidin is labile in the presence of oxidants at alkaline pH values. It also undergoes chlorophyll-sensitized photooxidation at a more acid pH. The products of the oxidation appear to have negligible activity in inhibiting electron transfer and photophosphorylation. Failure of desaspidin to uncouple in the presence of oxidants used as cofactors of noncyclic electron flow is presumably the result of this irreversible degradation of the desaspidin molecule during the early minutes of illumination or preincubation.